2011
DOI: 10.1111/j.1467-9604.2011.01499.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Coping Power Program in middle‐school children with disruptive behaviours and hyperactivity difficulties

Abstract: The purpose of this article is to discuss the effectiveness of the Coping Power Program (CPP); an evidencebased treatment delivered in a group format to at-risk middle-school children. Initially, two groups were randomised and formed: an intervention group of 24 CPP sessions and a control group. All students were enrolled in public schools from two rural counties in the United States. Out of the 119 total participants 63 (37 male) were in the intervention and 56 (35 male) were in the control group. From the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Bullying prevention and intervention programs that focus on cognitive and social functioning are important for changing passive intervention during bullying situations. A social‐cognitive intervention that targets children's cognitive processes and parental behaviors was found effective in reducing bullying (Jurecska et al, 2011). This study focuses on MD, SDO, and SE based SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bullying prevention and intervention programs that focus on cognitive and social functioning are important for changing passive intervention during bullying situations. A social‐cognitive intervention that targets children's cognitive processes and parental behaviors was found effective in reducing bullying (Jurecska et al, 2011). This study focuses on MD, SDO, and SE based SCT.…”
Section: Discussionmentioning
confidence: 99%
“…The responses of the various bystanders are central in influencing the frequency of bullying (Padgett & Notar, 2013; Salmivalli, 2010; Salmivalli et al, 2011; Wiesenthal, 2021) and are informed by several factors (Bauman et al, 2020), including the contextual, social, moral‐psychological, and motivational characteristics of the individuals involved. Social Cognitive Theory (SCT) is an essential theory for understanding the social and personal nature of involvement in bullying and has been used previously as a theoretical framework in the study of student bystander behaviors (Allison & Bussey, 2017; DeSmet et al, 2014); further, SCT interventions also have an empirical base (Jurecska et al, 2011). According to this theory, students who bully others exhibit a complex array of psychological, cognitive, and social characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term goal is the prevention of substance use (Lochman & Wells, 2002 ). Jurecska, Hamilton, and Peterson ( 2011 ) randomized two groups of students in four rural public schools. Teacher ratings indicated that there was a positive effect on student behavior in class.…”
Section: Examples Of Parent Training Programsmentioning
confidence: 99%
“…Coping Power intervention effects on multiple indices of problem behavior have also been found with youth diagnosed with disruptive behavior disorders [ 25 , 26 , 27 , 28 , 29 ], with students with behavior problems in dissemination and implementation studies in schools and community settings [ 30 , 31 , 32 , 33 , 34 , 35 ], and with children in other cultural environments [ 36 , 37 , 38 ]. When Coping Power has been implemented as a treatment for children with disruptive behavior disorders, it may also have a subsequent preventive effect for adolescent substance abuse and delinquent behavior.…”
Section: Introductionmentioning
confidence: 99%